Immune functions of pattern recognition receptors in Lepidoptera - Zhao, Lin; Niu, Jinlan; Feng, Disong; Wang, Xialu; Zhang, Rong (Frontiers in Immunology, 2023)
Pattern recognition receptors (PRRs), as the “sensors” in the immune response, play a prominent role in recognizing pathogen-associated molecular patterns (PAMPs) and initiating an effective defense response to pathogens in Lepidoptera. It is becoming increasingly clear that damage-associated molecular patterns (DAMPs) normally play a physiological role within cells; however, when exposed to extracellular, they may become “part-time” critical signals of the immune response. Based on research in recent years, we review herein typical PRRs of Lepidoptera, including peptidoglycan recognition protein (PGRP), gram-negative binding protein (GNBP), β-1,3-glucan recognition protein (βGRP), C-type lectin (CTL), and scavenger receptor (SR). We also outline the ways in which DAMPs participate in the immune response and the correlation between PRRs and immune escape. Taken together, these findings suggest that the role of PRRs in insect innate immunity may be much greater than expected and that it is possible to recognize a broader range of signaling molecules.